Reconstructing the Legal Limits of Itsbat Nikah: Dissenting Opinion, Child Marriage, and Doctrinal Development in Indonesian Islamic Family Law: Rekonstruksi Batas Hukum Itsbat Nikah: Pendapat Berbeda Hakim, Perkawinan Anak, dan Pengembangan Doktrin Hukum Keluarga Islam di Indonesia - Nur, Muliadi; Jamil, Abdul (Lex Renaissance, 2026)
Unregistered Muslim marriage in Indonesia creates a persistent tension between religious validity and state legal recognition, especially when the marriage was conducted while one party was underage and no prior marriage dispensation was obtained. This article examines Religious Court of Pasangkayu Decision No. 143/Pdt.P/2021/PA.Pky by positioning the dissenting opinion as the main doctrinal entry point for reconstructing the limits of itsbat nikah. The study uses normative legal research with statutory, case, and conceptual approaches. The court decision is treated as primary legal material containing legal facts, evidentiary assessment, judicial reasoning, interpretation of norms, majority reasoning, dissenting opinion, and legal conclusions. The article finds that the majority opinion reflects a post-factum protection model grounded in Islamic validity, marital continuity, administrative necessity, and children’s civil status. However, the dissenting opinion provides the article’s central novelty by formulating a preventive legality model that challenges the use of itsbat nikah as a retroactive substitute for marriage dispensation. The dissent shows that underage unregistered marriage cannot be treated as a mere registration defect because it implicates statutory safeguards against child marriage. Building on this dissenting reasoning, the article proposes a five-criteria doctrinal standard: Islamic validity, statutory legality, administrative necessity, child protection, and mafsadah-maslahah moral-hazard assessment. The article concludes that dissenting opinion can function as a source of doctrinal development in Islamic family law by limiting itsbat nikah without abandoning protection for vulnerable family members.